Orthopedic Sub-specialization: Need or Hype? Opinion from Nepalese Orthopedic Surgeons - Mishra, Bibhuti Nath; Poudel, Rishi Ram; Challa, Sravya (Journal of Nepal Health Research Council, 2021)
Background: In Nepal, the trend of rushing to orthopedic subspecialty fellowship is rising up. It’s debatable whether this pattern of practice is advancing orthopaedic care. There are issues with cost of subspecialty training and work satisfaction after it. Thus, this study aims to analyze orthopaedic surgeon’s prospect regarding subspecialty training in Nepal.Methods: This is a cross sectional observational study designed to take opinion of orthopaedic surgeons of Nepal regarding subspecialty practice in orthopedics. Structured closed ended questionnaire was designed in form of “Survey app” and was disseminated to maximum possible via electronic media.Results: Out of total 93 respondents (mean age 37.07 years), 45.7% had a subspecialty training. Among fellowship completed surgeons (42), mean duration of fellowship was 6.92 months, India was the commonest destination (53.49%), and Arthroscopy was highest followed by Spine and Arthroplasty. Among them who haven’t done fellowship (51), 100% mentioned to have interest in doing one. Maximum respondents recommended paid/sponsored fellowships (94.62%) and of 12 months’ duration (44.1%). Total of 97.85% agreed that fellowship training in orthopedics has really become important. Only 4.3% agreed that fellowship is an unnecessary burden/hype. Only 16.1% agreed that surgeons get detached from mainstream orthopedics after fellowship and also only 11.9% agreed that there retains any threat to mother orthopedics in future.Conclusions: With emerging practice of subspecialty in Orthopedics in Nepal, a six months’ duration fellowship and paid fellowship program is the major choice. Thus, the fraternity should work on to promote subspecialty practice and trainings.Keywords: Fellowship; orthopedics; subspecialty training